Food supplementation increases reproductive performance of ospreys in the lower Chesapeake Bay - Academia, Michael H.; Watts, Bryan D. (Frontiers in Marine Science, 2023)
The Atlantic States Marine Fisheries Commission (ASMFC), the governing body responsible for managing fisheries on the U.S. East Coast, formally adopted the use of Ecological Reference Points (ERPs) for Atlantic menhaden, Brevoortia tyrannus. Scientists and stakeholders have long recognized the importance of menhaden and predators such as ospreys, Pandion haliaetus, that support the valuable ecotourism industry and hold cultural significance. Landings in the reduction fishery are at their lowest levels and menhaden is facing potential localized depletion. Mobjack Bay, located within the lower Chesapeake Bay, has been a focus of osprey research since 1970 and represents a barometer for the relationship between osprey breeding performance and the availability of their main prey, menhaden. Since local levels of menhaden abundance were not available, we conducted a supplemental menhaden feeding experiment on osprey pairs during the 2021 breeding season. Our main objective was to determine if the delivery rate of menhaden had an influence on nest success and productivity. Nest success (χ2 = 5.5, df = 1, P = 0.02) and productivity (β = 0.88, SE = 0.45, CI = 0.049, 1.825, P = 0.048) were significantly higher within the treatment group. Reproductive rates within the control group were low and unsustainable suggesting that current menhaden availability is too low to support a demographically stable osprey population. Menhaden populations should be maintained at levels that will sustain a stable osprey population in which they are able to produce 1.15 young/active nest to offset mortality.